Bilirubin Levels in Cases of Neonatal Jaundice Treated with Phototherapy at Kalisat Hospital - Sasmito, Lulut; Suparwati, Ratna; Putri, Herlidian; Luthfiana, Lia Ulfah (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
abstract